Dual-flow-RootChip reveals local adaptations of roots towards environmental asymmetry at the physiological and genetic levels - Stanley, Claire; Brugman, Rik; Großmann, Guido (The new phytologist, 2018)
Roots grow in highly dynamic and heterogeneous environments. Biological activity as well as uneven nutrient availability or localized stress factors result in diverse microenvironments. Plants adapt their root morphology in response to changing environmental conditions, yet it remains largely unknown to what extent developmental adaptations are based on systemic or cell-autonomous responses. We present the dual-flow-RootChip, a microfluidic platform for asymmetric perfusion of Arabidopsis roots to investigate root-environment interactions under simulated environmental heterogeneity. Applications range from investigating physiology, root hair development and calcium signalling upon selective exposure to environmental stresses to tracing molecular uptake, performing selective drug treatments and localized inoculations with microbes. Using the dual-flow-RootChip, we revealed cell-autonomous adaption of root hair development under asymmetric phosphate (Pi) perfusion, with unexpected repression in root hair growth on the side exposed to low Pi and rapid tip-growth upregulation when Pi concentrations increased. The asymmetric root environment further resulted in an asymmetric gene expression of RSL4, a key transcriptional regulator of root hair growth. Our findings demonstrate that roots possess the capability to locally adapt to heterogeneous conditions in their environment at the physiological and transcriptional levels. Being able to generate asymmetric microenvironments for roots will help further elucidate decision-making processes in root-environment interactions.
First published: 10 November 2017
Gesehen am 17.08.2018